2006
DOI: 10.1073/pnas.0604318103
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive localized delivery of Herceptin to the mouse brain by MRI-guided focused ultrasound-induced blood–brain barrier disruption

Abstract: Antibody-based anticancer agents are promising chemotherapeutic agents. Among these agents, Herceptin (trastuzumab), a humanized anti-human epidermal growth factor receptor 2 (HER2͞ c-erbB2) monoclonal antibody, has been used successfully in patients with breast cancer. However, in patients with brain metastasis, the blood-brain barrier limits its use, and a different delivery method is needed to treat these patients. Here, we report that Herceptin can be delivered locally and noninvasively into the mouse cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
462
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 600 publications
(473 citation statements)
references
References 29 publications
8
462
1
2
Order By: Relevance
“…The first obstacle is the selectively permeable BBB, which hampers the transport and diffusion of large molecules (>500 Da) from the vasculature into the brain, thus reducing the effects of chemotherapeutic agents against the malignant brain tumors 11. Recently, focused ultrasound (FUS) combined with microbubbles (MB), has been increasingly recognized as a noninvasive strategy to induce transient, reversible, and local BBB disruption 12. The biosafety and effectiveness have also been demonstrated by numerous preclinical studies 13.…”
Section: Introductionmentioning
confidence: 99%
“…The first obstacle is the selectively permeable BBB, which hampers the transport and diffusion of large molecules (>500 Da) from the vasculature into the brain, thus reducing the effects of chemotherapeutic agents against the malignant brain tumors 11. Recently, focused ultrasound (FUS) combined with microbubbles (MB), has been increasingly recognized as a noninvasive strategy to induce transient, reversible, and local BBB disruption 12. The biosafety and effectiveness have also been demonstrated by numerous preclinical studies 13.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have shown that the BBB disruption (BBBD) lasts for a few hours (Hynynen et al 2001;Hynynen et al 2005;Hynynen et al 2006) and can be reliably applied with negligible damage to the brain parenchyma (Hynynen et al 2001;Hynynen et al 2005;McDannold et al 2005;Hynynen et al 2006), at least when compared to invasive techniques. Studies have also shown that the BBBD can be performed using low ultrasound frequencies (0.26 MHz and 0.69 MHz) suitable for trans-cranial application with a focused beam Hynynen et al 2006), and that delivery of chemotherapy (Treat et al 2005) and antibodies can be achieved (Kinoshita et al 2006b;Kinoshita et al 2006a). …”
Section: Introductionmentioning
confidence: 99%
“…However, MRI contrast agents could be useful for monitoring. Studies investigating the delivery of chemotherapy agents (76) and antibodies (77,78) have found an association between the amount of agent delivered to the brain with the amount of contrast enhancement (Fig. 7).…”
Section: Bbb Openingmentioning
confidence: 98%
“…It can also be applied at frequencies suitable for a transcranial application (73,75). The focal, anatomically selective opening acts as a virtual needle that can be noninvasively used for any selected target, such as noninvasive targeted drug delivery (76,77). Examples of MRI showing focal BBB opening in a rabbit brain are shown in Fig.…”
Section: Bbb Openingmentioning
confidence: 99%